CTL-BASED SKI LEARNING WITH VIRTUAL FIELD TRIPS AND MULTIMEDIA AT MAN LANDAK - Dewi Sulistyowati; Wahab Wahab (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to describe the implementation of the Contextual Teaching and Learning (CTL) model integrated with Virtual Field Trips (VFT) and multimedia, as well as to explore its impact on student motivation and learning outcomes in the Islamic Cultural History (SKI) subject at MAN Landak. This research employs a qualitative approach with a descriptive case study design. Data collection techniques include participant observation, in-depth interviews, and documentation studies, which were then analyzed using the interactive model by Miles, Huberman, and Saldana, and validated through source and technique triangulation. The results indicate a fundamental transformation from a conventional learning pattern to a constructivist pattern that positions students as active subjects. The dynamics of student learning activities consistently increased from the moderate category (score 2.8) in the first meeting to the very good category (score 3.7) in the final meeting. Additionally, the average motivation score increased by 1.2 points, with the highest increase observed in the curiosity aspect, and student learning outcomes experienced a significant improvement, where the